REFLECTIONS OF PHRASES IN THE WORKS OF UTKIR HOSHIMOV (Archive of Conferences, 2021)
This article discusses the analysis of phraseological units in the works of O’tkir Hoshimov, the importance of phrases in the works, as well as the creative phrases of the writer, their differences from the common phrases.